Identification of multiple cracks in 2D elasticity by means of the reciprocity principle and cluster analysis. (15th December 2017) - Shifrin, Efim I; Kaptsov, Alexander V
Abstract: An inverse 2D elastostatic problem is considered. It is assumed that an isotropic, linear elastic body can contain a finite number of rectilinear, well-separated cracks. The surfaces of the cracks are assumed to be free of the loads. A method is developed for reconstruction the cracks by means of the applied loads and displacements on the boundary of the body, obtained in a single static test. The method is based on the reciprocity principle, elements of the theory of distributions, and cluster analysis. Numerical examples are considered.